Digital Economy: Challenges and Threats for Modern Russia - GRETCHENKO, A. I.; GOROKHOVA, I. V.; DEMENKO, O. G.; GRETCHENKO, A. A. (Journal of Advanced Research in Law and Economics, 2018)
The article describes the positive and negative aspects of transfer to the digital economy. An overview of literature regarding the digitization of society is presented. Preconditions for further digitization and economic development in Russia are stated. The beginning of the 21st century was marked by the flourishing of digital technologies, based on information revolution and economic globalization. Information has become the main resource in the society and in economic processes. People turn information into knowledge, and socioeconomic relations are increasingly transferred into a network environment. The key factor of digital transformation in the activities of the market players is the development of the digital culture.